Djuna Barnes' antihumanist reproduction. Issue 9 (1st September 2020) - Richardson, Laura K.
ABSTRACT: Anti-teleological reproduction is a Barnesian aesthetic that bridges both content and practice in Djuna Barnes' late work. Contrary to a scholastic tradition that reads Barnes' revision practices as barriers to her success as an author, this essay understands her obsessive relationship with iteration as a key component of her oeuvre. In its refusal of traditional goals of authorship, namely completion and publishing, Barnes' late work betrays the Enlightenment expectation that literature and its authors conform to models of progress, teleology, and rationality in the realm of aesthetics and public persona. These characteristics emerge in Barnes' late play The Antiphon (1958), where the compulsive restaging of an original trauma abjures catharsis in favour of 'pointless', antihumanist reproductions.